GEOLOGY AND STATIC 3-D RESERVOIR MODELLING ON MELIAT FORMATION, AI FIELD, TARAKAN BASIN, NORTH KALIMANTAN PROVINCE - Ichsan, Abdurrachman
AI Field is a gas field that is administratively located in North Kalimantan Province and geologically located in Tertiary Tarakan Basin. The purposes of this study are to determine the depositional environment, facies distribution, geological structures, petrophysics properties distribution, and hydrocarbon reserves on the study interval. Study interval consists of three sandstone reservoirs on Meliat Formation. Data used in this study consist of wireline log and completion log data from six wells on AI field, six 2D seismic lines with NE-SW direction, six 2D seismic lines with NW-SE direction, checkshot data from AI-4 and AI-7 wells, core description from AI-3 and AI-4 wells, and also biostratigraphy report from AI-1 well. Methods used in this study consist of well data analysis, seismic data analysis, reservoir modelling, and hydrocarbon reserves estimation. Based on analysis on well log, core description, and biostratigraphy report data, study interval might consists of distributary channel, tidal mouth bar, and deltaic shale. Study interval itself was probably deposited on tidal-dominated delta environment. Then, based on seismic data analysis, there are sinistral transform faults that are associated with NW-SE anticlines and three reverse faults that are associated with NE-SW anticlines. 3D static reservoir modelling consists of structural modelling, facies modelling, and petrophysics property modelling. From reservoir modelling, we can identify reservoir geometry, facies distribution, petrophysics property distribution, and total of hydrocarbon reserves estimation. The result of reserves estimation is that the study interval has a total of 3.387 BSCF initial gas in place (IGIP).